2016
DOI: 10.1371/journal.pone.0166487
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition of Protein Fibrillation by Proline and Sorbitol: Biophysical Investigations

Abstract: We report here interesting synergistic effects of proline and sorbitol, two well-known chemical chaperones, in the inhibition of fibrillation of two proteins, insulin and lysozyme. A combination of many biophysical techniques has been used to understand the structural morphology and modes of interaction of the chaperones with the proteins during fibrillation. Both the chaperones establish stronger polar interactions in the elongation and saturation stages of fibrillation compared to that in the native stage. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…In another study, Choudhary et al reported the inhibition of the protein fibrillation of lysozyme and insulin by proline and sorbitol. 376 Proline contains a closed ring structure in its side chain which has a hydrophobic surface, which enables it to interact with proteins through hydrophobic interactions.…”
Section: Small Moleculesmentioning
confidence: 99%
“…In another study, Choudhary et al reported the inhibition of the protein fibrillation of lysozyme and insulin by proline and sorbitol. 376 Proline contains a closed ring structure in its side chain which has a hydrophobic surface, which enables it to interact with proteins through hydrophobic interactions.…”
Section: Small Moleculesmentioning
confidence: 99%
“…Sorbitol may act as a protein chaperone. Indeed, sorbitol has been recently reported to inhibit protein fibrillation and stabilize misfolded polypeptides (Choudhary, Save, Kishore, & Hosur, 2016; Roy & Bhat, 2018), Interestingly, it has been postulated that the decreased yield of properly folded PMP22 at the cell membrane may be a driver for CMT1A characteristic dysmyelination (Mittendorf et al., 2017; Schlebach et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This needs further detailed residue‐level analysis. Generally, the synergistic effect of mixture of osmolytes enhances the solubility of proteins and inhibits protein fibril formation as well …”
Section: Figurementioning
confidence: 99%
“…Generally, the synergistic effect of mixture of osmolytes enhances the solubility of proteins [13] and inhibits protein fibril formation as well. [14] Similarly, the extent of destabilization attained by the proteins against Gdm-induced denaturation (ΔΔG unf ), in the presence of varying concentrations of Arg, was also calculated. ΔΔG unf = (ΔG unf in the presence of Arg -ΔG unf in the absence of Arg).…”
mentioning
confidence: 99%